O preconceito aos imigrantes no acesso a serviços de saúde: uma revisão integrativa - Sousa, Leonardo Lucas da Silva de (2022)
Prejudice is a human experience, built in the daily life of relationships, however it produces direct and indirect influences on the health and illness process among the groups that experience it. One of these groups are immigrants, bordering or not, who are negatively discriminated against because of their place of birth or appearance or way of being. Based on the above, this dissertation aimed to “Know, understand and analyze the scientific evidence on the prejudice suffered by immigrants in accessing health services”. When questioning the issue of this user's access to local health systems in different territories and spaces of the world, we sought to understand how, when and in what way prejudice can have implications on the lives of users as immigrants, especially in the attempt to indicate an ethical commitment to be followed, which respects human rights and reflects aspects of universal health. Through the integrative literature review method, the theoretical debate on prejudice was viable, based on three organized categories from the articles found at the end of the review, namely: a) Prejudice as a barrier to access to health for immigrants; b) The living and health conditions of immigrants who suffer prejudice; c) The denial of the right to health as a manifestation of prejudice. The theoretical discussion was still supported by the contributions of the authors Lukács, Heller and Chauí when discussing daily life and prejudice. Thus, this work presents, at the end, the relevance of recognizing and coping with this phenomenon, understood as part of everyday thinking and behavior, indicating the most favorable practices and conditions where this occurs, especially in the health sector.